Composite negative electrode material for low-temperature lithium ion battery, preparation method and application

By tin antimonide composite and carbon coating modification, the composite negative electrode material is formed, which solves the problem of capacity attenuation and lithium-ion battery under low temperature conditions, and achieves high energy density and good cycle stability.

CN119812258AActive Publication Date: 2025-04-11SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411953476.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing lithium-ion batteries exhibit capacity attenuation, lithium-ion risk and safety problems under low temperature conditions, making it difficult to meet the application needs under high energy density and extreme conditions.

Method used

The dual modification methods of phosphorus composite and carbon coating are used to modify tin antimonide to form a composite negative electrode material for low-temperature lithium-ion batteries, improving its electrochemical performance.

Benefits of technology

It realizes high specific capacity and fast charging characteristics, maintains good cycle stability and safety under extreme conditions, and significantly improves low-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812258A_ABST
    Figure CN119812258A_ABST
Patent Text Reader

Abstract

The invention discloses a composite negative electrode material for a low-temperature lithium ion battery as well as a preparation method and application of the composite negative electrode material for the low-temperature lithium ion battery. According to the composite negative electrode material for the low-temperature lithium ion battery, tin antimonide is modified by adopting dual modification means of phosphorus compounding and carbon coating, so that the composite negative electrode material has relatively good electrochemical performance; and the material still has relatively good cycling stability and safety under extreme conditions, so that excellent low-temperature performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-ion battery materials, and specifically relates to a composite negative electrode material for low-temperature lithium-ion batteries, and also relates to a preparation method of the composite negative electrode material for low-temperature lithium-ion batteries and its application as a negative electrode material. Background Art

[0002] In recent years, lithium-ion batteries have become a key energy storage device receiving significant attention and research due to their high energy density, stable cycle performance, and zero-memory performance. Their application scenarios are constantly expanding, with applications in key areas such as grid storage, national defense, space, and deep-sea operations. However, when lithium-ion batteries are used in certain extreme applications, such as deep-sea operations and polar expeditions, lithium deposition occurs due to the drastically reduced electrochemical reaction kinetics. Therefore, in order to substantially improve the energy density, cycle life, and safety performance of lithium-ion batteries under low-temperature conditions, the negative electrode material, which plays a decisive role in battery performance, must maintain good performance under extreme conditions, becoming a research hotspot in the lithium-ion battery field.

[0003] Currently, graphite is the most widely commercialized anode material for lithium-ion batteries, but it is increasingly unable to meet the current demand for high energy density in lithium-ion batteries. More seriously, graphite's low lithium insertion potential and slow lithium ion diffusion at low temperatures lead to rapid capacity decay at low temperatures and the risk of dendrite growth. Furthermore, graphite's low theoretical specific capacity and safety concerns regarding lithium deposition at low temperatures seriously hinder the application of lithium-ion batteries in applications requiring high energy density and under extreme conditions. To achieve lithium-ion batteries that can operate normally at low temperatures, finding a suitable anode material to replace graphite has become a key issue.

[0004] As a very important type of negative electrode material for lithium-ion batteries, tin-based negative electrode materials have the advantages of high specific capacity, moderate lithium insertion potential, and abundant resources. Unlike the deintercalation mechanism of graphite negative electrodes, tin-based negative electrodes mainly store lithium through alloying and conversion reactions, are less inhibited by low temperatures, and have a low risk of lithium precipitation under low-temperature fast-charging conditions. In particular, the antimony and tin in tin antimonide, a binary tin alloy material, can provide a buffer for each other's volume expansion during the deintercalation and deintercalation of lithium at different potentials, and have better cycle stability than pure tin. However, negative electrode materials based on tin antimonide have the defects of volume expansion and particle pulverization during the cycle, and lack a fixed and stable diffusion channel during the deintercalation and deintercalation of lithium. How to take advantage of the low risk of lithium precipitation under low-temperature fast-charging conditions to improve it so that it has better electrochemical performance as a negative electrode material has become a new research direction in the field of low-temperature lithium-ion batteries. Summary of the Invention

[0005] In view of this, the present invention provides a composite negative electrode material for a low-temperature lithium-ion battery. The composite negative electrode material for a low-temperature lithium-ion battery adopts a dual modification method of phosphorus composite and carbon coating to modify tin antimonide and has better electrochemical performance, overcoming the problems existing in the above-mentioned tin antimonide as a negative electrode material.

[0006] In a first aspect of the present invention, a composite negative electrode material for a low-temperature lithium-ion battery is provided, comprising tin antimonide, phosphorus, and expanded graphite, wherein the expanded graphite covers the tin antimonide and phosphorus.

[0007] In the composite negative electrode material for low-temperature lithium-ion batteries of the present invention, the electrochemical performance of the negative electrode material is improved by a dual modification method of phosphorus composite and carbon coating, wherein the use of phosphorus can be used as an active material to improve the overall specific capacity on the one hand, and on the other hand, the kinetics of tin antimonide deintercalation and lithium insertion can be regulated. At the same time, the presence of phosphorus causes the negative electrode material to produce Li3P in the electrode electrochemical reaction, which shows a high affinity and ionic conductivity for lithium ions, and lithium ions have a low coordination number on the Li3P surface, making it easier for lithium ions to desolvate and diffuse into the interior of the electrode material through the solid electrolyte membrane (SEI). In particular, by coating with expanded graphite, on the one hand, direct contact between the electrolyte and the tin antimonide active material can be prevented, thereby preventing the continuous decomposition of the electrolyte and the growth of the surface film. On the other hand, a buffer can be provided for the volume expansion of the tin antimonide active material during the deintercalation and lithium insertion process, preventing the agglomeration and growth of the tin antimonide active material particles. Therefore, the composite negative electrode material for low-temperature lithium-ion batteries of the present invention has high specific capacity and fast charging characteristics, and still has good cycle stability and safety under extreme conditions, thereby obtaining excellent low-temperature performance.

[0008] Preferably, in the composite negative electrode material for low-temperature lithium-ion batteries, based on the total mass of the composite negative electrode material for low-temperature lithium-ion batteries, the amount of tin antimonide is 60-85%, the amount of phosphorus is 7-10%, and the amount of expanded graphite is 9-30%. Further preferably, the amount of tin antimonide is 65-80%, the amount of phosphorus is 7-10%, and the amount of expanded graphite is 10-30%.

[0009] In the composite negative electrode material for a low-temperature lithium-ion battery of the present invention, the tin antimonide serves as the matrix material, exhibiting excellent electronic and ionic conductivity. Phosphorus is highly dispersed within or on the surface of the material. Phosphorus participates in the formation of the SEI, generating Li3P that reduces the desolvation energy of lithium ions and promotes ionic conduction. Furthermore, phosphorus participates in the alloying process between the electrode material and lithium, regulating and accelerating the alloying process between the tin antimonide and lithium. Furthermore, the appropriate amount of expanded graphite coated with phosphorus and tin antimonide can suppress their volume expansion during charge and discharge, increasing the stability of the composite negative electrode material and preventing the dissolution of charge and discharge products and reactions with the electrolyte, thereby enhancing the battery's cycling stability.

[0010] Preferably, in the composite negative electrode material for low-temperature lithium-ion batteries, the phosphorus may be red phosphorus and / or blue phosphorus.

[0011] In the present invention, the thickness of the expanded graphite layer can be adjusted according to the size of the phosphorus and tin antimonide used as core materials, or can be specifically adjusted according to the amount of expanded graphite used or performance requirements. It is necessary to form an expanded graphite layer that completely covers the phosphorus and tin antimonide. This layer can prevent direct contact between the electrolyte and the tin antimonide active material, thereby preventing the continuous decomposition of the electrolyte and the growth of the surface film. At the same time, it can provide a buffer for the volume expansion of the tin antimonide active material during the lithium insertion and extraction process, preventing the agglomeration and growth of the tin antimonide active material particles. However, it is also necessary to avoid the coating layer being too thick, which may lead to a decrease in battery performance, such as affecting the release of active lithium.

[0012] Preferably, in the present invention, the particle size of the composite negative electrode material for a low-temperature lithium-ion battery is 1-15 μm, more preferably 3-10 μm. If the particle size of the composite negative electrode material for a low-temperature lithium-ion battery is large, the particles will be severely pulverized; if the particle size of the composite negative electrode material for a low-temperature lithium-ion battery is small, it will have a higher specific surface area, which will intensify the reaction with the electrolyte.

[0013] Preferably, in the composite negative electrode material for low-temperature lithium-ion batteries, the mass ratio of the tin antimonide to the phosphorus is (7-10):1.

[0014] In the composite negative electrode material for low-temperature lithium-ion batteries of the present invention, the tin antimonide partially forms a chemical bond with phosphorus, and partially forms a system with properties similar to an alloy after being highly dispersed, ensuring sufficient contact between the two, fully leveraging the advantages of both, and overcoming each other's shortcomings. Specifically, the high theoretical specific capacity and extremely low lithium ion diffusion energy barrier of the phosphorus material, the high specific capacity, moderate lithium insertion potential and suitability for low-temperature conditions of tin antimonide are all maintained, and a negative electrode material for lithium-ion batteries suitable for extreme conditions that can achieve both high energy density and fast charging performance can be obtained. In addition, the composite conductive network of tin antimonide and phosphorus and the carbon coating method overcome the defects of particle pulverization of tin antimonide and volume expansion of tin antimonide and phosphorus. Obviously, the composite negative electrode material for low-temperature lithium-ion batteries of the present invention provides prospects for further expanding the application scope of lithium-ion batteries.

[0015] In a second aspect of the present invention, a method for preparing the composite negative electrode material for a low-temperature lithium-ion battery is provided. The method comprises: first, ball-milling tin antimonide and phosphorus to obtain a preliminary composite; then, adding expanded graphite and performing a second ball-milling to obtain the composite negative electrode material for a low-temperature lithium-ion battery of the present invention.

[0016] It is clear that in the preparation method of the present invention, a dual-modified composite negative electrode material of phosphorus composite and carbon coating is obtained through two-step ball milling. First, the first step of ball milling is to compound tin antimonide with phosphorus. During this ball milling process, the tin antimonide and phosphorus partially form chemical bonds, and the remaining part is highly dispersed to form an alloy-like dispersion system, constructing an internal composite conductive network. Subsequently, expanded graphite is added for a second step of ball milling. During this process, the expanded graphite coats the preliminary composite formed in the first step of ball milling. The resulting composite negative electrode material for low-temperature lithium-ion batteries retains the advantages of these single-component materials while overcoming their respective disadvantages, providing hard conditions for the application of lithium-ion batteries under extreme conditions.

[0017] In the above method, the ball milling is carried out by conventional ball milling methods in the art, such as tumbling ball milling, swing ball milling, grinding ball milling, high-energy ball milling, and the like.

[0018] Preferably, in the above method, the grinding balls used in the ball mill are zirconium balls, i.e., zirconium oxide grinding balls, to avoid contamination of raw materials. The diameter of the grinding balls is conventional in this field, which can be 5 mm, 8 mm, etc., and the ball-to-material ratio can be 25-50:1.

[0019] Preferably, in the above method, the grinding balls used in the ball mill need to be cleaned before use, such as using one or more of anhydrous ethanol, acetone, and isopropanol for cleaning. Specifically, they can be cleaned once or multiple times, such as 2 times, 3 times or more. After cleaning, they also need to be dried to remove liquid residue on the surface. The cleaning can prevent impurities such as powder attached to the periphery of the grinding balls from affecting the raw materials and thus affecting the performance of the product.

[0020] Preferably, in the above method, the ball milling process needs to be carried out under an inert gas. Furthermore, the inert gas is one or more of high-purity nitrogen, argon, and helium to prevent the heat generated during the ball milling process from causing the raw materials to react in an oxygen environment.

[0021] Preferably, in the above method, the single continuous ball milling time does not exceed 30 minutes, preferably 10-30 minutes, the room temperature cooling is not less than 10 minutes, preferably 10-30 minutes, and the ball milling speed is 900-1200 rpm.

[0022] Preferably, in the above method, the cumulative milling time of the first ball milling step is 3-8 hours, and the cumulative milling time of the second ball milling step is 3-8 hours. During the ball milling process, the grinding balls generate heat due to collision. Long-term continuous ball milling can cause the temperature inside the ball mill to be too high, affecting the properties of the material.

[0023] For example, in the above method, the ball milling method used is oscillating ball milling, the ball mill speed is 900-1200 rpm, and a bidirectional intermittent operation mode is adopted, that is, alternating forward and reverse rotations, each ball milling time is 10 minutes, and the machine is stopped for 10 minutes.

[0024] More specifically, when the ball milling is performed using an oscillating ball mill, the method for preparing the composite negative electrode material for a low-temperature lithium-ion battery of the present invention is as follows:

[0025] S1. The first step of ball milling: the tin antimonide and phosphorus are loaded into an oscillating ball mill and loaded with grinding balls with a ball-to-material ratio of 25-50:1, filled with inert gas and sealed in an oscillating mill for oscillating ball milling to obtain a complex of tin antimonide and phosphorus, that is, a preliminary complex;

[0026] S2. The second step of ball milling: The ball milling jar of step S1 is opened in an inert atmosphere, expanded graphite is added, and then sealed and the second step of ball milling is performed to obtain a low-temperature lithium-ion battery composite negative electrode material.

[0027] The inert gas is one or more of high-purity nitrogen, argon, and helium. The ball mill speed of the oscillating ball mill is 900-1200 rpm. The cumulative ball milling time for each step is 3-8 hours. A bidirectional intermittent operation mode is adopted, that is, alternating forward and reverse rotations. The ball milling time for each step is 10 minutes, and the machine is shut down for 10 minutes.

[0028] The grinding balls need to be cleaned before use, for example, using one or more of anhydrous ethanol, acetone, and isopropyl alcohol for one or more cleanings.

[0029] In addition, it should be noted that, in the method of the present invention, the ball milling methods used in the first ball milling and the second ball milling may be the same or different, but in order to avoid unnecessary trouble, it is preferred to use the same ball milling method in the same ball mill.

[0030] Preferably, in the method for preparing the composite negative electrode material for a low-temperature lithium-ion battery, based on the total mass of the composite negative electrode material for a low-temperature lithium-ion battery, the amount of tin antimonide is 60-85%, the amount of phosphorus is 7-10%, and the amount of expanded graphite is 9-30%. Due to the poor conductivity of phosphorus, the amount of phosphorus used should be limited. Excessive use of expanded graphite as a coating material can reduce the capacity of the composite material, while too little can result in poor coating effects.

[0031] Preferably, in the preparation method of the composite negative electrode material for a low-temperature lithium-ion battery, based on the total mass of the composite negative electrode material for a low-temperature lithium-ion battery, the amount of tin antimonide is 65-80%, the amount of phosphorus is 7-10%, and the amount of expanded graphite is 10-30%.

[0032] In the preparation method of the composite negative electrode material for low-temperature lithium-ion batteries, the thickness of the expanded graphite layer coated with phosphorus and tin antimonide can be adjusted according to the size of phosphorus and tin antimonide as the core materials, and can also be specifically adjusted according to the usage amount of expanded graphite or performance requirements.

[0033] Preferably, in the preparation method of the present invention, the particle size of the obtained composite negative electrode material for a low-temperature lithium-ion battery is 1-15 μm, more preferably 3-10 μm. If the particle size of the obtained composite negative electrode material for a low-temperature lithium-ion battery is large, the particles are severely pulverized; if the particle size of the composite negative electrode material for a low-temperature lithium-ion battery is small, it has a higher specific surface area, which will intensify the reaction with the electrolyte.

[0034] Preferably, in the method for preparing the composite negative electrode material for low-temperature lithium-ion batteries, the mass ratio of tin antimonide added in the first ball milling to the phosphorus is (7-10):1.

[0035] It is obvious that the preparation method of the composite negative electrode material for low-temperature lithium-ion batteries of the present invention can prepare a composite negative electrode material for low-temperature lithium-ion batteries with higher specific capacity and better cycle performance and good low-temperature performance through a simple and process-controllable ball milling method, and this method has the potential for large-scale production.

[0036] In a third aspect of the present invention, a negative electrode plate for a lithium-ion battery is provided, wherein the negative electrode plate contains the above-mentioned composite negative electrode material for a low-temperature lithium-ion battery.

[0037] Preferably, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, the negative electrode material layer includes a negative electrode active material and a binder, and the negative electrode active material includes the above-mentioned composite negative electrode material for low-temperature lithium-ion batteries.

[0038] Further preferably, the mass proportion of the composite negative electrode material for low-temperature lithium-ion batteries in the negative electrode material layer may be greater than or equal to 60 wt%, for example, 70-80 wt%, 80-90 wt%, 75 wt%, and the like.

[0039] Still more preferably, the negative electrode material layer may further include a conductive agent.

[0040] In the above-mentioned negative electrode sheet, the negative electrode current collector is conventional in the art. Further preferably, the negative electrode current collector includes, but is not limited to, a metal foil or alloy foil, the surface of which may be etched or roughened to form a secondary structure to facilitate effective contact with the negative electrode material layer. Exemplary metal foils may be copper foil or carbon-coated copper foil, and exemplary alloy foils may be stainless steel foil, carbon-coated stainless steel foil, or copper alloy foil.

[0041] In the above-mentioned negative electrode sheet, the amounts and types of the binder and conductive agent are conventional in the art. For example, the binder may specifically include, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), lithium polyacrylate (Li-PAA), polyacrylate, polyacrylamide (PAM), polyimide (PI), etc. The conductive agent may specifically include, but is not limited to, one or more of acetylene black, Ketjen black, SuperP conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, Super C65, and single-walled carbon nanotubes (SWCNTs).

[0042] In addition, in the negative electrode plate of the present invention, the negative electrode active material may further include other negative electrode active components, including but not limited to one or more of lithium titanate, carbon-based materials, silicon-based materials, tin-based materials, germanium-based materials, antimony-based materials, and bismuth-based materials. Among them, carbon-based materials may include graphite (such as natural graphite, artificial graphite), non-graphitizable carbon (soft carbon, hard carbon, etc.); silicon-based materials may include one or more of elemental silicon, silicon-based alloys, silicon oxides, and silicon-carbon composite materials; tin-based materials may include one or more of elemental tin, tin alloys, and tin oxides; germanium-based materials may include one or more of elemental germanium, germanium alloys, germanium-carbon composites, and germanium oxides; antimony-based materials include one or more of elemental antimony and antimony alloys; bismuth-based materials include one or more of elemental bismuth and bismuth alloys.

[0043] Other negative electrode active components can be dispersed together with the composite negative electrode material for low-temperature lithium-ion batteries of the present invention in the negative electrode material layer. The two can exist independently or in the form of a composite material.

[0044] The negative electrode plate of the present invention uses the composite negative electrode material for low-temperature lithium-ion batteries of the present invention, and has high specific capacity and stability when performing charge and discharge cycles at low temperatures.

[0045] In a fourth aspect of the present invention, a method for preparing the negative electrode sheet for the above-mentioned lithium ion battery is provided, which comprises the following steps:

[0046] SF1 prepares negative electrode slurry: negative electrode active material, binder, and optional conductive agent are uniformly mixed in a solvent to form negative electrode slurry;

[0047] SF2 coating of negative electrode slurry: The negative electrode slurry prepared in step SF1 is coated on the negative electrode current collector, and then dried to obtain the negative electrode sheet for the lithium-ion battery.

[0048] Obviously, the preparation method of the present invention is simple, easy to implement, and can be prepared on a large scale. The method of preparing the negative electrode slurry in step SF1 is conventional in the art, such as preparing the slurry by a high-speed stirring degassing machine.

[0049] Preferably, the solvent used in step SF1 is water, an alcohol solvent, an amide solvent, an ether solvent or the like, and the amount used is also the amount used in the art.

[0050] Further preferably, the negative electrode active material comprises the composite negative electrode material for low-temperature lithium-ion batteries of the present invention and optional other negative electrode active components, and the other negative electrode active components include, but are not limited to, one or more of lithium titanate, carbon-based materials, silicon-based materials, tin-based materials, germanium-based materials, antimony-based materials, and bismuth-based materials. Among them, carbon-based materials may include graphite (such as natural graphite, artificial graphite), non-graphitizable carbon (soft carbon, hard carbon, etc.); silicon-based materials may include one or more of elemental silicon, silicon-based alloys, silicon oxides, and silicon-carbon composite materials; tin-based materials may include one or more of elemental tin, tin alloys, and tin oxides; germanium-based materials may include one or more of elemental germanium, germanium alloys, germanium-carbon composites, and germanium oxides; antimony-based materials include one or more of elemental antimony and antimony alloys; bismuth-based materials include one or more of elemental bismuth and bismuth alloys.

[0051] The other negative electrode active components can be dispersed together with the composite negative electrode material for low-temperature lithium-ion batteries of the present invention in the negative electrode material layer. The two can exist independently or in the form of a composite material.

[0052] Further preferably, in the negative electrode material layer formed by coating the above-mentioned negative electrode slurry on the negative electrode current collector, the mass percentage of the negative electrode active material in the negative electrode material layer is greater than or equal to 60wt%, and further preferably, the mass percentage of the composite negative electrode material for the low-temperature lithium-ion battery of the present invention in the negative electrode material layer is greater than or equal to 60wt%, for example, 70-80wt%, 80-90wt%, 75% and the like.

[0053] In the above method, the negative electrode current collector is conventional in the art. Further preferably, the negative electrode current collector includes, but is not limited to, a metal foil or alloy foil, the surface of which may be etched or roughened to form a secondary structure to facilitate effective contact with the negative electrode material layer. Exemplary metal foils may be copper foil or carbon-coated copper foil, and exemplary alloy foils may be stainless steel foil, carbon-coated stainless steel foil, or copper alloy foil.

[0054] In the above method, the amounts and types of the binder and conductive agent are conventional amounts and types in the art. For example, the binder may specifically include, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), lithium polyacrylate (Li-PAA), polyacrylate, polyacrylamide (PAM), polyimide (PI), etc. The conductive agent may specifically include, but is not limited to, one or more of acetylene black, Ketjen black, Supper P conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, Super C65, and single-walled carbon nanotubes (SWCNTs).

[0055] Preferably, in the above method, in step SF1, the mass ratio of the negative electrode active material, binder, and conductive agent is (7.5-8.5): (0.75-1.25): (0.75-1.25). At this ratio, the negative electrode sheet has better performance and can be better applied to extreme conditions.

[0056] Preferably, in the above method, in step SF2, the negative electrode slurry prepared in step SF1 is coated on the negative electrode current collector to a thickness of 100 μm to 250 μm.

[0057] Preferably, in the above method, in step SF2, the negative electrode current collector coated with the negative electrode slurry needs to be rolled after drying, and the rolling thickness is 60-80% of the thickness of the electrode sheet after drying. After rolling, the active material can be in closer contact, preventing the active material and the current collector from losing contact after being soaked in the electrolyte.

[0058] Preferably, in the above method, in step SF2, the negative electrode current collector coated with the negative electrode slurry is dried by conventional drying methods in the art, such as oven drying, air drying, etc., and there is no strict limitation, as long as the purpose can be achieved.

[0059] In a fifth aspect of the present invention, a battery made using the above-mentioned negative electrode plate is provided, which includes the above-mentioned negative electrode plate.

[0060] The shape of the battery of the present invention is not particularly limited and can be cylindrical, button (coin) type, flat, square, etc. It can be used in conventional terminal consumer products and can also be used in certain application fields under extreme conditions such as deep-sea operations, polar scientific research, etc.

[0061] Compared with the prior art, the present invention modifies tin antimonide by a dual means of phosphorus compounding and carbon coating, wherein the use of phosphorus can be used as an active material to increase the overall specific capacity on the one hand, and on the other hand, it can also regulate the kinetics of tin antimonide lithium deintercalation. At the same time, the presence of phosphorus causes the negative electrode material to produce Li3P in the electrode electrochemical reaction. This substance shows a high affinity and ionic conductivity for lithium ions, and lithium ions have a low coordination number on the Li3P surface, making it easier for lithium ions to desolvate and diffuse into the interior of the electrode material through the solid electrolyte membrane (SEI); at the same time, the coating of expanded graphite can prevent direct contact between the electrolyte and the tin antimonide active material, thereby preventing the continuous decomposition of the electrolyte and the growth of the surface film. On the other hand, it can also provide a buffer for the volume expansion of the tin antimonide active material during the lithium deintercalation process, preventing the agglomeration and growth of the tin antimonide active material particles. Therefore, the composite negative electrode material for low-temperature lithium-ion batteries of the present invention has high specific capacity and fast charging characteristics, and still has good cycle stability and safety under extreme conditions, thereby obtaining excellent low-temperature performance.

[0062] Furthermore, the present invention efficiently prepares the composite negative electrode material for low-temperature lithium-ion batteries using only a simple ball milling method. The preparation process is simple and controllable, requiring no additional equipment design. The two-step ball milling method not only achieves a better composite effect of tin antimonide and phosphorus, but also achieves a better coating effect of expanded graphite. In the composite negative electrode material for low-temperature lithium-ion batteries, phosphorus regulates the lithium intercalation and deintercalation process of the tin antimonide alloy, accelerating its alloying reaction with lithium. Phosphorus also has a high specific capacity, which can increase the overall capacity of the negative electrode. Expanded graphite, as a carbon source, achieves a good coating effect by regulating the proportion used, allowing the material to maintain better cycle stability during cycling. Ultimately, the composite negative electrode material for low-temperature lithium-ion batteries described in the present invention exhibits high specific capacity and stability during charge-discharge cycles at low temperatures, enabling the production of charge-discharge batteries suitable for use under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 X-ray diffraction spectra of the negative electrode materials prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention;

[0064] Figure 2 Scanning electron microscope images of the negative electrode materials prepared in Example 1, Example 2, and Example 3;

[0065] Figure 3 The room temperature charge and discharge curves of the negative electrode materials prepared in Example 1, Example 2, and Example 3;

[0066] Figure 4 Figure 1 is a room temperature charge and discharge cycle diagram of the negative electrode materials prepared in Example 1, Example 2, and Example 3;

[0067] Figure 5 Scanning electron microscope images of the negative electrode materials prepared in Comparative Examples 1 and 2;

[0068] Figure 6 The room temperature charge and discharge curves of the negative electrode materials prepared in Comparative Examples 1 and 2 are shown;

[0069] Figure 7 The room temperature charge and discharge cycle diagram of the negative electrode materials prepared in Comparative Examples 1 and 2;

[0070] Figure 8 Scanning electron microscope images of the negative electrode materials prepared in Comparative Examples 3 and 4;

[0071] Figure 9 The room temperature charge and discharge curves of the negative electrode materials prepared in Comparative Examples 3 and 4;

[0072] Figure 10The room temperature charge and discharge cycle diagram of the negative electrode materials prepared in Comparative Examples 3 and 4;

[0073] Figure 11 This is a charge and discharge cycle diagram of the negative electrode material prepared in Example 2 at low temperature. DETAILED DESCRIPTION

[0074] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the specific implementation will be explained below in conjunction with the accompanying drawings as needed.

[0075] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0076] The raw materials used in the following examples are all commercially available. For example, the tin antimonide was purchased from Zhengzhou Alpha Company, the phosphorus was purchased from Aladdin Biochemical Technology Co., Ltd., and the expanded graphite was purchased from Henan Liugong Graphite Co., Ltd.

[0077] Example

[0078] Example 1

[0079] A Preparation of Composite Anode Materials for Low-Temperature Lithium-Ion Batteries

[0080] S1 The first step of ball milling: add 0.9g of tin antimonide powder and 0.1g of red phosphorus powder into an oscillating ball mill, seal the can under argon protection, and then perform oscillating ball milling. The ball mill is filled with zirconium oxide grinding balls with a mass ratio of 30:1 to the raw materials. The ball milling parameters are set as follows: the working mode is "bidirectional intermittent operation, timed shutdown" mode, the oscillating ball mill speed is 1000rpm, the total ball milling time is 5h, of which the forward running time is 10min, the intermittent running time is 10min, and then the reverse running time is 10min. This is a cycle. After running 15 times, a complex of tin antimonide and phosphorus, i.e., a preliminary complex, can be obtained.

[0081] S2: The second step of ball milling: the ball milling jar used in the first step of ball milling is opened under an argon protection environment, and 0.1 g of expanded graphite is added thereto. The ball milling jar is then sealed and ball milling is continued. The ball milling method is the same as that in step S1. After ball milling, a composite negative electrode material for low-temperature lithium-ion batteries can be obtained, which is recorded as T-SPG1.

[0082] Figure 1 The X-ray diffraction pattern of the T-SPG1 composite material prepared in this example shows that its crystal structure is consistent with that of SnSb, which is a rhombohedral crystal system and an R-3m structure. Figure 2a is an image of the T-SPG1 negative electrode material prepared in this example under a scanning electron microscope, which shows particles with expanded graphite sheets coated on the surface.

[0083] B Preparation of negative electrode sheets for lithium-ion batteries

[0084] SF1 prepares the negative electrode slurry: 0.4g of the T-SPG1 prepared above, 0.05g of the binder (sodium carboxymethyl cellulose CMC) and 0.05g of the conductive agent (Super C65 and SWCNT, the mass ratio of the two is 50:1) are uniformly mixed, and 3.5g of deionized water is used as the solvent, and a slurry is prepared by a high-speed stirring degassing machine to obtain the negative electrode slurry;

[0085] SF2-coated negative electrode slurry: The prepared negative electrode slurry is evenly coated on battery-grade copper foil with a coating thickness of 150μm. After drying in a vacuum drying oven at 80°C for 10 hours to completely remove water, the T-SPG1 negative electrode sheet is obtained by punching out 12mm discs. The active material loading of T-SPG1 is about 1.5mg / cm 2 .

[0086] C. The T-SPG1 negative electrode sheet prepared in this example was prepared into a button battery with metallic lithium as the counter electrode and the electrochemical performance was tested.

[0087] SC1 Preparation of isolation film: punch out 19mm Celgard2325 as isolation film, and dry the isolation film in a vacuum oven to remove residual moisture.

[0088] SC2 preparation of button-type CR2016 half-cell: This step needs to be carried out in an argon-filled glove box (Shanghai Mikaelona Electromechanical Technology Co., Ltd.), and the water and oxygen content must be strictly controlled to be less than 0.01 ppm. The negative electrode, isolation membrane, and metal lithium counter electrode are assembled in this order, and the electrolyte is used to fully infiltrate them separately. Subsequently, they are assembled into a button-type CR2016 half-cell. The electrolyte used is a solution of 1 mol / L lithium hexafluorophosphate in a 1:1:1 volume ratio of ethylene carbonate, ethyl methyl carbonate, and propylene carbonate, with 10% by volume of fluoroethylene carbonate added.

[0089] SC3 electrochemical performance test: The button-type CR2016 half-cell prepared by SC2 was subjected to room temperature constant current charge and discharge tests under the following conditions in a LAND CT2001A battery testing system: the charge and discharge current density was 200mA / g and 1000mA / g, the voltage range was 0.01V~2V, and the charge and discharge process was as follows: first, the voltage was discharged to 0.01V at a current density of 200mA / g and allowed to stand for 3 minutes. Then, the voltage was charged to 2V at a current density of 200mA / g and the activation was repeated 3 times. Starting from the fourth cycle, the charge and discharge test was carried out at a current density of 1000mA / g.

[0090] It should be noted that when calculating the capacity retention rate, the fourth cycle, i.e. the first cycle after activation stabilization, is used as the basis for calculation.

[0091] Figure 3 The first charge and discharge curve of the battery prepared using the T-SPG1 negative electrode material prepared in this example showed that its first discharge specific capacity was 886 mAh / g and its first coulombic efficiency was 88.24%. Figure 4 It includes a room temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 597.6mAh / g and the capacity retention rate is 71.3%.

[0092] Example 2

[0093] A Preparation of Composite Anode Materials for Low-Temperature Lithium-Ion Batteries

[0094] The composite negative electrode material for a low-temperature lithium-ion battery of this embodiment was prepared in the manner described in Example 1, with the only difference being that the amount of expanded graphite used in the second ball milling step S2 was 0.2 g. The obtained composite negative electrode material for a low-temperature lithium-ion battery was designated as T-SPG2.

[0095] Figure 1 The X-ray diffraction pattern of the T-SPG2 composite material prepared in this example shows that its crystal structure is consistent with that of SnSb, which is a rhombohedral crystal system and an R-3m structure. Figure 2 b is an image of the T-SPG2 negative electrode material prepared in this example under a scanning electron microscope, which shows particles with expanded graphite sheets coated on the surface.

[0096] B Preparation of negative electrode sheets for lithium-ion batteries

[0097] The negative electrode sheet for the lithium ion battery of this embodiment is prepared in the manner described in Example 1, with the only difference being that the composite negative electrode material for the low-temperature lithium ion battery used is T-SPG2.

[0098] C. The T-SPG2 negative electrode sheet prepared in this example was prepared into a button battery with metallic lithium as the counter electrode and the electrochemical performance was tested.

[0099] The T-SPG2 negative electrode sheet prepared in this example was formed into a button cell with metallic lithium as the counter electrode in the manner described in Example 1 and the electrochemical performance test was performed.

[0100] Figure 3 The first charge and discharge curve of the battery prepared using the T-SPG2 negative electrode material prepared in this example showed that its first discharge capacity was 815 mAh / g and its first coulombic efficiency was 87.10%. Figure 4 It includes a room temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 646.5mAh / g and the capacity retention rate is 83.2%.

[0101] D. The T-SPG2 negative electrode prepared in this example was prepared into a button battery with metal lithium as the counter electrode and subjected to low-temperature charge and discharge tests.

[0102] The T-SPG2 negative electrode prepared in this example was molded into a button-type battery with lithium metal as the counter electrode, following the method described in Example 1. The only difference was that the electrolyte used in this example was a solution of 1 mol / L lithium hexafluorophosphate dissolved in a 1:1 volume ratio of tetrahydrofuran and dimethyltetrahydrofuran. The battery was tested in a thermostat at -10°C and -30°C. The low-temperature charge and discharge tests were conducted at a current density of 200 mA / g and a voltage range of 0.01 V to 2 V.

[0103] Figure 11 The charge and discharge cycle diagram of Example 2 at low temperature is shown, showing relatively high capacity and cycle stability at low temperature.

[0104] Example 3

[0105] A Preparation of Composite Anode Materials for Low-Temperature Lithium-Ion Batteries

[0106] The composite negative electrode material for a low-temperature lithium-ion battery of this embodiment was prepared in the manner described in Example 1, with the only difference being that the amount of expanded graphite used in the second ball milling step S2 was 0.3 g. The obtained composite negative electrode material for a low-temperature lithium-ion battery was designated as T-SPG3.

[0107] Figure 1 The X-ray diffraction pattern of the T-SPG3 composite material prepared in this example shows that its crystal structure is consistent with that of SnSb, which is a rhombohedral crystal system and an R-3m structure. Figure 2 b is an image of the T-SPG3 negative electrode material prepared in this example under a scanning electron microscope, which shows particles with expanded graphite sheets coated on the surface, and it can be found that there are many uncompounded graphite sheets.

[0108] B Preparation of negative electrode sheets for lithium-ion batteries

[0109] The negative electrode sheet for the lithium ion battery of this embodiment is prepared in the manner described in Example 1, with the only difference being that the composite negative electrode material for the low-temperature lithium ion battery used is T-SPG3.

[0110] C. The T-SPG3 negative electrode prepared in this example was prepared into a button battery with metallic lithium as the counter electrode and the electrochemical performance was tested.

[0111] The T-SPG3 negative electrode sheet prepared in this example was formed into a button cell with metallic lithium as the counter electrode in the manner described in Example 1 and the electrochemical performance test was performed.

[0112] Figure 3 The first charge-discharge curve of the T-SPG3 negative electrode material prepared in this example showed that its first discharge specific capacity was 738.5 mAh / g and its first coulombic efficiency was 81.66%. Figure 4 It includes a room temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 494.3mAh / g and the capacity retention rate is 78.9%.

[0113] Comparative Example

[0114] Comparative Example 1

[0115] A Preparation of Composite Anode Materials for Lithium-ion Batteries

[0116] First, 0.9g of tin antimonide powder and 0.1g of red phosphorus powder were added to a vibrating ball mill, followed by the addition of 0.1g of expanded graphite. The mixture was sealed and canned under argon protection and then subjected to vibrating ball milling. The ball mill was filled with zirconia grinding balls at a mass ratio of 30:1 to the raw materials. The ball milling parameters were set as follows: the working mode was "bidirectional intermittent operation, timed shutdown" mode, the vibrating ball mill speed was 1000rpm, the total ball milling time was 5h, of which the forward running time was 10min, the intermittent running time was 10min, and the reverse running time was 10min. This was a cycle, and after 15 runs, the negative electrode powder was obtained, recorded as SPG1.

[0117] Figure 1 The X-ray diffraction pattern of the SPG1 composite material prepared in this comparative example shows that its crystal structure is consistent with that of SnSb, which is a rhombohedral crystal system and an R-3m structure. Figure 5 a is an image of the SPG1 negative electrode material prepared in this comparative example under a scanning electron microscope, which shows particles with expanded graphite sheets covering the surface, but the expanded graphite sheets fail to completely cover the particles.

[0118] B Preparation of negative electrode sheets for lithium-ion batteries

[0119] The negative electrode sheet for the lithium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the composite negative electrode material for the low-temperature lithium ion battery used was SPG1.

[0120] C. The SPG1 negative electrode prepared in this comparative example was prepared into a button battery with metallic lithium as the counter electrode and the electrochemical performance was tested.

[0121] The SPG1 negative electrode sheet prepared in this comparative example was formed into a button cell with metallic lithium as the counter electrode in the manner described in Example 1 and the electrochemical performance test was performed.

[0122] Figure 6 The first charge-discharge curve of the SPG1 negative electrode material prepared in this comparative example showed that its first discharge specific capacity was 842.8 mAh / g and its first coulombic efficiency was 87.68%. Figure 7 It includes a room temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 443.7mAh / g and the capacity retention rate is 55.8%.

[0123] Comparative Example 2

[0124] A Preparation of Composite Anode Materials for Lithium-ion Batteries

[0125] The composite negative electrode material for lithium ion battery of this comparative example was prepared in the manner described in Comparative Example 1, with the only difference being that the amount of expanded graphite used in the ball milling step was 0.2 g. The obtained composite negative electrode material for lithium ion battery was recorded as SPG2.

[0126] Figure 1 The X-ray diffraction pattern of the SPG2 composite material prepared in this experiment shows that its crystal structure is consistent with that of SnSb, which is a rhombohedral crystal system and R-3m structure. Figure 5 b is an image of the SPG2 negative electrode material prepared in this comparative example under a scanning electron microscope, showing particles with expanded graphite sheets coated on the surface, but the coating effect is poor.

[0127] B Preparation of negative electrode sheets for lithium-ion batteries

[0128] The negative electrode sheet for the lithium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the composite negative electrode material for the lithium ion battery used was SPG2.

[0129] C. The SPG2 negative electrode prepared in this comparative example was prepared into a button battery with metallic lithium as the counter electrode and the electrochemical performance was tested.

[0130] The SPG2 negative electrode sheet prepared in this comparative example was formed into a button cell with metallic lithium as the counter electrode in the manner described in Example 1 and the electrochemical performance test was performed.

[0131] Figure 6 The first charge-discharge curve of the SPG2 negative electrode material prepared in this comparative example showed that its first discharge specific capacity was 558.3 ​​mAh / g and its first coulombic efficiency was 77.17%. Figure 7 It includes a room temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 394.6mAh / g and the capacity retention rate is 68.9%.

[0132] Comparative Example 3

[0133] A Preparation of Composite Anode Materials for Lithium-ion Batteries

[0134] The composite negative electrode material for lithium ion batteries of this comparative example was prepared in the manner described in Example 1, with the only difference being that no red phosphorus was added in the first ball milling step S1, and only antimony tin powder was added. The obtained composite negative electrode material for lithium ion batteries was recorded as SPG3.

[0135] Figure 1 The X-ray diffraction pattern of the SPG3 negative electrode material prepared in this comparative example is a rhombohedral crystal system with an R-3m structure. Figure 8 a is an image of the SPG3 negative electrode material prepared in this comparative example under a scanning electron microscope.

[0136] B Preparation of negative electrode sheets for lithium-ion batteries

[0137] The negative electrode sheet for the lithium ion battery of this embodiment is prepared in the manner described in Example 1, with the only difference being that the composite negative electrode material for the low-temperature lithium ion battery used is SPG3.

[0138] C. The SPG3 negative electrode prepared in this comparative example was prepared into a button battery with lithium metal as the counter electrode and the electrochemical performance was tested.

[0139] The SPG3 negative electrode sheet prepared in this comparative example was formed into a button cell with metallic lithium as the counter electrode in the manner described in Example 1 and the electrochemical performance test was performed.

[0140] Figure 9 The first charge and discharge curve of the SPG3 negative electrode material prepared in this example has an initial discharge capacity of 660.7 mAh / g and an initial coulombic efficiency of 86.47%. Figure 10 It includes a normal temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 58.1mAh / g and the capacity retention rate is only 9.6%.

[0141] Comparative Example 4

[0142] A Preparation of Composite Anode Materials for Lithium-ion Batteries

[0143] 0.9 g of tin antimonide powder and 0.1 g of red phosphorus powder were added to an oscillating ball mill, sealed and canned under argon protection, and then oscillating ball milling was performed. The ball mill was filled with zirconia grinding balls with a mass ratio of 30:1 to the raw materials. The ball milling parameters were set as follows: the working mode was "bidirectional intermittent operation, timed shutdown" mode, the oscillating ball mill speed was 1000 rpm, the total ball milling time was 5 h, of which the forward operation time was 10 min, the intermittent operation time was 10 min, and then the reverse operation time was 10 min. This was a cycle. After 15 times of operation, a complex of tin antimonide and phosphorus, namely a preliminary complex, was obtained as a composite negative electrode material for lithium-ion batteries, which was recorded as SP.

[0144] Figure 1 The X-ray diffraction pattern of the SP negative electrode material prepared in this comparative example shows that its crystal structure is consistent with that of SnSb, which is a rhombohedral crystal system and an R-3m structure. Figure 8 b is the image of the SP negative electrode material prepared in this comparative example under a scanning electron microscope.

[0145] B Preparation of negative electrode sheets for lithium-ion batteries

[0146] The negative electrode sheet for the lithium ion battery of this comparative example was prepared in the manner described in Example 1, with the only difference being that the composite negative electrode material for the low-temperature lithium ion battery used was SP.

[0147] C. The SP negative electrode sheet prepared in this comparative example was prepared into a button battery with metallic lithium as the counter electrode and the electrochemical performance was tested.

[0148] The SP negative electrode sheet prepared in this comparative example was formed into a button cell with metallic lithium as the counter electrode in the manner described in Example 1 and the electrochemical performance test was performed.

[0149] Figure 9 The first charge-discharge curve of the SP negative electrode material prepared in this comparative example showed that its first discharge specific capacity was 906.4 mAh / g and its first coulombic efficiency was 88.34%. Figure 10 It includes a normal temperature charge and discharge cycle diagram. After 150 cycles, the discharge capacity is 58.7mAh / g and the capacity retention rate is only 6.4%.

[0150] The above embodiments and comparative examples specifically demonstrate the universality and effectiveness of the present invention in improving the electrochemical performance of negative electrode materials for low-temperature lithium-ion batteries from the aspects of different material compositions and different preparation methods, and prove that the composite negative electrode material for low-temperature lithium-ion batteries obtained by means of phosphorus composite and carbon coating has high specific capacity and good cycle stability. Example 2 of the present invention has considerable specific capacity and cycle stability at low temperatures of -10°C and -30°C, which provides a material basis for realizing lithium-ion batteries with high energy density, high rate performance and good low-temperature performance, and has certain inspiration and help for breaking through the problem of low-temperature fast charging of lithium-ion batteries.

[0151] Based on the disclosure and teachings of the above description, those skilled in the art may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and any modifications and variations of the invention should also fall within the scope of protection of the claims of the present invention. In addition, although certain specific terms are used in this description, these terms are for convenience of description only and do not constitute any limitation to the present invention.

Claims

1. A composite negative electrode material for a low-temperature lithium-ion battery, characterized in that: The invention comprises tin antimonide, phosphorus and expanded graphite, wherein the expanded graphite covers the tin antimonide and phosphorus.

2. The composite negative electrode material for low-temperature lithium-ion batteries according to claim 1, characterized in that: Based on the total mass of the composite negative electrode material for low-temperature lithium-ion batteries, the amount of tin antimonide is 60-85%, the amount of phosphorus is 7-10%, and the amount of expanded graphite is 9-30%.

3. The composite negative electrode material for low-temperature lithium-ion batteries according to claim 1, characterized in that: The phosphorus is red phosphorus and / or blue phosphorus.

4. The composite negative electrode material for low-temperature lithium-ion batteries according to claim 1, characterized in that: Based on the total mass of the composite negative electrode material for low-temperature lithium-ion batteries, the amount of tin antimonide is 65-80%, the amount of phosphorus is 7-10%, and the amount of expanded graphite is 10-30%.

5. The composite negative electrode material for low-temperature lithium-ion batteries according to claim 1, characterized in that: The particle size of the composite negative electrode material for low-temperature lithium-ion batteries is 1-15 μm, more preferably 3-10 μm.

6. The composite negative electrode material for low-temperature lithium-ion batteries according to claim 1, characterized in that: The mass ratio of the tin antimonide to the phosphorus is (7-10):

1.

7. A method for preparing the composite negative electrode material for a low-temperature lithium-ion battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: firstly, ball milling tin antimonide and phosphorus to obtain a preliminary composite; then adding expanded graphite and performing a second ball milling to obtain the composite negative electrode material for a low-temperature lithium-ion battery of the present invention.

8. The method according to claim 7, characterized in that The ball milling process needs to be carried out under an inert gas. Furthermore, the inert gas is one or more of high-purity nitrogen, argon, and helium.

9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate contains the composite negative electrode material for a low-temperature lithium-ion battery according to any one of claims 1 to 6.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Preparation method of graphene-loaded and carbon-coated tin-antimony lithium battery cathode material

    CN102324497A

  • Composite negative electrode material, negative electrode plate, secondary battery and electronic equipment

    CN116072863A

  • METHOD FOR MANUFACTURING COMPOSITE INCLUDING Sn-Sb COMPOUND AND TRANSITION METAL CARBIDE USING TERNARY TRANSITION METAL-Sn-Sb ALLOY AS PRECURSOR, AND NEGATIVE ELECTRODE MATERIAL FOR SECONDARY BATTERY HAVING THE COMPOSITE MANUFACTURED THEREBY

    KR101948682B1

  • Secondary lithium ion battery containing a prelithiated anode

    US20100173198A1